Female genital mutilation/cutting in Sierra Leone: are educated women intending to circumcise their daughters? - Edward Kwabena Ameyaw; Justice Kanor Tetteh; Ebenezer Kwesi Armah-Ansah; Kofi Aduo-Adjei; Aisha Sena-Iddrisu (BMC, 2020)
Abstract Background Female genital mutilation/cutting (FGM/C) has been recognized as a gross violation of human rights of girls and women. This is well established in numerous international legal instruments. It forms part of the initiation ceremony that confers womanhood in Sierra Leone. Girls and women who are subjected to this practice are considered to be ready for marriage by their parents and communities and are rewarded with celebrations, gifts, and public recognition. Following this, we examined the relationship between education and women's FGM/C intention for their daughters in Sierra Leone. Methods We used cross-sectional data from the women's file of the 2013 Sierra Leone Demographic and Health Survey (SLDHS) to explore the influence of education on FGM/C intention among women in the reproductive age (15-49). A sample of 6543 women were included in the study. Our analysis involved descriptive computation of education and FGM/C intention. This was followed by a two-level multilevel analysis. Fixed effect results were reported as Odds Ratios and Adjusted Odds Ratios with their respective credible intervals (CrIs) whilst results of the random effects were presented as variance partition coefficients and median odds ratios. Results Our findings showed that women who had no formal education were more likely to intend to circumcise their daughters [aOR = 4.3, CrI = 2.4-8.0]. Among the covariates, women aged 20-24 [aOR = 2.3, CrI = 1.5-3.4] were more likely to intend to circumcise their daughters compared to women between 45 and 49 years old. Poorest women were more likely to report intention of circumcising their daughters in the future compared with the richest [aOR = 2.1, CrI = 1.3-3.2]. We noted that, 63.3% of FGM/C intention in Sierra Leone is attributable to contextual factors. Conclusion FGM/C intention is more common among women with no education, younger women as well as women in the lowest wealth category. We recommend segmented female-child educational and pro-poor policies that target uneducated women in Sierra Leone. The study further suggests that interventions to end FGM/C need to focus on broader contextual and social norms in Sierra Leone.